Benchmark of a self-consistent dynamic 1D divertor model DIV1D using the 2D SOLPS-ITER code. (1st December 2022) - Derks, G L; Frankemölle, J P K W; Koenders, J T W; van Berkel, M; Reimerdes, H; Wensing, M; Westerhof, E
Abstract: This paper presents DIV1D, a new 1D dynamic physics-based model of the divertor plasma under development to study and control the dynamics of detached plasmas. An innovative feature of DIV1D is that it mimics cross-field transport using an effective flux expansion and includes a neutral gas background outside the divertor leg. We outline a 1D mapping procedure for static 2D SOLPS-ITER simulations of divertor plasmas in the Tokamak á Configuration Variable, which can be used to benchmark 1D codes. For DIV1D good agreement is found for the most important divertor plasma quantities along the leg (e.g., densities temperature, heat flux, and velocity) both in a qualitative and quantitative sense. In addition, the comparison with SOLPS-ITER demonstrates that DIV1D self-consistently captures the evolution of divertor plasma quantities in the main heat flux channel as a function of the upstream plasma density in a scan from 2 to 3 × 10 19 m − 3 . The agreement is ascribed to the unique account of cross-field transport in DIV1D with an effective flux expansion and the interaction with an external neutral gas background.